Disleksia dan Literasi Digital : Implementasi Media Digital dalam Bimbingan Membaca - Alfi Khoiriyah; Dwi Nafiatun Nisaus Sholikah; Qoiril Anif; Yeri Utami (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Reading difficulties or dyslexia are learning disorders that affect a person's ability to recognize letters, words, or texts accurately and quickly. This study aims to identify effective guidance methods in helping individuals with dyslexia overcome their challenges. The research approach used is qualitative with a literature study method, which includes an analysis of various sources of theory and practice related to dyslexia. The results of the study indicate that the theory of dyslexia consists of the Phonology theory and the Double Deficit Theory. Teaching methods for children with dyslexia, namely the Fernald method, the Gilingham method, the Grass Analysis method, the Hegge-Kirk-Kirk method and the Neurological Impress method, personalized guidance, early intervention, the use of assistive technology, and a multisensory approach can improve the reading ability of individuals with dyslexia. These findings are expected to be a reference for educators, parents, and practitioners to develop more inclusive and effective guidance strategies in supporting the development of children with dyslexia.